2019
DOI: 10.1111/apa.14797
|View full text |Cite
|
Sign up to set email alerts
|

Neonatologists and neonatal nurses have positive attitudes towards perinatal end‐of‐life decisions, a nationwide survey

Abstract: Aim Perinatal death is often preceded by an end‐of‐life decision (ELD). Disparate hospital policies, complex legal frameworks and ethically difficult cases make attitudes important. This study investigated attitudes of neonatologists and nurses towards perinatal ELDs. Methods A survey was handed out to all neonatologists and neonatal nurses in all eight neonatal intensive care units in Flanders, Belgium in May 2017. Respondents indicated agreement with statements regarding perinatal ELDs on a Likert‐scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…Recent data in the literature shows increased frequency of withholding or withdrawing treatment [ 24 , 25 ]. EURONIC multicentre ethical research study and subsequent studies showed that withholding or withdrawing treatment is a common practice in several European NICUs and worldwide [ 1 , 14 , 26 29 ] One out of three till five physicians decided withholding of treatment, while one out of ten decided withdrawing of treatment: these ratios are lower than these reported in other European countries and much similar to that in South Mediterranean countries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data in the literature shows increased frequency of withholding or withdrawing treatment [ 24 , 25 ]. EURONIC multicentre ethical research study and subsequent studies showed that withholding or withdrawing treatment is a common practice in several European NICUs and worldwide [ 1 , 14 , 26 29 ] One out of three till five physicians decided withholding of treatment, while one out of ten decided withdrawing of treatment: these ratios are lower than these reported in other European countries and much similar to that in South Mediterranean countries.…”
Section: Discussionmentioning
confidence: 99%
“…Since the predictable outcome/ undesirable consequence of certain symptom relief practices might be a hastened death, the dividing line between 'palliative care' and 'unethical killing' is crucially essential, both ethically and legally. Neonatal euthanasia is legal in the Netherlands [22] and in a Belgium study it was concluded that physicians and nurses feel that it is acceptable, in certain cases, to administer medication with the explicit intention of hastening death [23]. Public faith in the medical profession and in the field of palliative medicine requires that we differentiate between clinicians and murderers, and healthcare deserves the clearest guidance about what distinguishes lawful from unlawful conduct [21].…”
Section: The 'Devils' Choice'mentioning
confidence: 99%
“…We adapted the questionnaire used in a similar previous study 31 The third part of the questionnaire examined the behavioral intentions of respondents in two specific, well-defined hypothetical cases. These cases were developed by two experts in prenatal diagnosis.…”
Section: Questionnairementioning
confidence: 99%